Development of morphology-dependent nanoselenium carriers for enhancing biological activity and reducing plant stress - Jingyuan Wang; Ronggang Zhai; Yifan Ma; Haoyu Chen; Danyang Jing; Huaiyu Yang; Yi Wang (Ecotoxicology and Environmental Safety)
Owing to their small size, morphology and release modification properties, nanopesticides are considered promising alternative strategies for enhancing biological activity and minimizing pesticide losses. In this study, we used a colloidal self-assembly method to develop a morphology-stable, regularly rod-shaped nanoselenium pesticide carrier (NSer), which was further modified with chitosan. After loading penthiopyrad (PEN), the biological activity of NSer@PEN and its impact on the physiological and biochemical processes of plants were further compared with those of spherical nanoselenium pesticides (NSes@PEN) and commercial materials (20 % PEN SC). The biological activities were quantified through the EC50 values, which revealed that NSer@PEN (0.71 mg/L) and NSes@PEN (1.09 mg/L) exhibited significantly greater activity against Colletotrichum orbiculare Arx compared to 20 % PEN SC (2.70 mg/L). Moreover, through further investigation into the impact of nanopesticides on plant root exudates, Fourier transform infrared spectroscopy (FTIR) and two-dimensional correlation spectroscopy (2D-COS) analysis revealed that the ketone CO bond exhibited the strongest binding affinity, and the CO bond of phenols contributed significantly to the binding of cucumber root exudates induced by NSer@PEN, resulting in a mild response of the plant. The morphology-dependent nanoselenium carriers developed in this work are expected to enhance biological activity and reduce plant stress caused by pesticides, tackling one of the application challenges of pesticides.